Study of Biological Excess Sludge Reduction in Sequencing Batch Reactor by Heating the Reactor - Takdastan, Afshin; Pazoki, Maryam (Asian Journal of Chemistry, 2010)
The municipal wastewater sludge has been identified as a hazardous waste. Thus stabilization and sanitation of sludge prior to discharge into the environment and its reuse in accordance with environmental laws are inevitable. An ideal way to solve sludge-associated problems is reducing sludge formation in the wastewater purification process rather than the post-treatment of the generated sludge. Most biological wastewater treatment processes are temperature sensitive; therefore increasing process temperature is effective for reducing sludge production. Main objective of this research is to reduce sludge production during wastewater treatment process which can contribute to reduction in excess sludge treatment and disposal challenges in wastewater treatment plants due to economic, environmental and regulation factors. In this research, two sequencing batch reactors with the capacity of 20 L, controlled by on-line system were used. Long term (6 months) continuous experiments were conducted to identify the influence of controlled up-shifting of temperature from 40 to 60 °C within the reactor during the reaction phase on reduction of biological excess sludge. Once steady state condition established in the reactors, samples were taken and analyzed for COD, BOD5, TSS, MLSS, SOUR, SVI and Y coefficient. Results showed that when temperature increased from 23 to 45 °C, during the solid retention time of 10 days, the kinetic yield coefficient decreased from 0.63 to 0.46. In the other word, the excess sludge was reduced by ca. 27 %. While, the soluble COD increased slightly in the effluent and the removal percentage decreased from 89 in the control reactor to 63 in the test reactor. The amount of SVI and SOUR in the mentioned temperature reduced to 50 mL/g and 12 mgO2/h gVSS, respectively. At 60 °C, no sludge was observed, while effluent SCOD and turbidity increased considerably and exceeded the APHA wastewater disposal standard.